Computer Safety, Reliability, and Security 35th International Conference, SAFECOMP 2016, Trondheim, Norway, September 21-23, 2016, Proceedings - Skavhaug, Amund; Guiochet, Jérémie; Bitsch, Friedemann (Programming and Software Engineering, 2016)
This book constitutes the refereed proceedings of the 35th International Conference on Computer Safety, Reliability, and Security, SAFECOMP 2016, held in Trondheim, Norway, in September 2016. The 24 revised full papers presented were carefully reviewed and selected from 71 submissions. The papers are organized in topical sections on fault injection, safety assurance, formal verification, automotive, anomaly detection and resilience, cyber security, fault trees, and safety analysis.